ナトリウム-グルコース共輸送体のサブタイプ阻害が虚血および薬理学的プレコンディショニングによる心保護効果に与える影響 - 江頭, 崇 (Springer Nature, 2024)
Nagasaki University (長崎大学) 博士(医学) Background: Sodium-glucose cotransporter (SGLT) 2 inhibitors partially inhibit SGLT1 expression; however, whether a clinical dose of SGLT2 inhibitor abrogates ischemic preconditioning (IPC) is unknown, and the pharmacological cardioprotective effect under SGLT1 inhibition has not been examined. In this study, we investigated whether a clinical dose of tofogliflozin abrogates IPC and whether pharmacological preconditioning with olprinone has cardioprotective effects under SGLT1 inhibition. Methods: Male Wistar rats were divided into seven groups (seven rats per group) and subjected to the following treatments before inducing ischemia/reperfusion (I/R; 30 minutes of coronary artery occlusion followed by 120 minutes of reperfusion): saline infusion control treatment (Con); ischemic preconditioning (IPC); IPC after phlorizin infusion (IPC+Phl); IPC after low-dose tofogliflozin infusion (IPC+L-Tof); IPC after high-dose tofogliflozin infusion (IPC+H-Tof); olprinone infusion (Olp); and Olp infusion after phlorizin infusion (Olp+Phl). Results: The infarct size was significantly decreased in the IPC group, but not in the IPC+Phl group. In contrast, the infarct size decreased in the IPC+L-Tof and IPC+H-Tof groups. Additionally, Olp reduced the infarct size, and the effect was preserved in Olp+Phl groups. Phosphorylated AMP-activated protein kinase (AMPK) expression was lower in the IPC+Phl group compared to that in the IPC group. Conclusion: The cardioprotective effect of IPC was attenuated by strong SGLT1 inhibition, but the effect was preserved under a clinical dose of highly selective SGLT2 inhibitor. Olprinone exerts a cardioprotective effect even under strong SGLT1 inhibition. 長崎大学学位論文 学位記番号:博(医歯薬)甲第1633号 学位授与年月日:令和6年9月4日 Author: Takashi Egashira • Taiga Ichinomiya • Akihiro Yokoyama • Sojiro Matsumoto • Ushio Higashijima • Motohiro Sekino • Hiroaki Murata • Osamu Yoshitomi • Shuntaro Sato • Tetsuya Hara Citation: Cureus, 16(5), art. no. e59757; 2024 Nagasaki University ...